A critical review for applying three-dimensional concrete wall printing technology in Egypt. (3rd September 2019) - Geneidy, Omar; Ismaeel, Walaa S.E.; Abbas, Ayman
ABSTRACT: The Three-dimensional printing (3DP) for concrete construction has risen as a new technology, yet, it has limited application in countries due to a number of reasons. Accordingly, this study articulates around integrating manual labour for 3D printing of cementious-based materials as an initial stage for promoting this advanced technology in middle and low-income countries like Egypt. This hybrid 3DP/manual labour system is investigated as a small scale lab test application for wall construction through extrusion-based 3D concrete printing. Moreover, different concrete mixes are tested to ensure structural validity and integrity while increasing precision and design flexibility. This integrated qualitative and quantitative methodology adds insights to the growing body of knowledge concerning the applicability of using 3DP wall construction as a replacement for their traditional known form with limited budget and manual integration. This shows that the technology can still be tailored according to different conditional limitations, including; material, cost and operating system.